Lipid Mediators, M2 Macrophages, and Pathological Neovascularization. Issue 12 (December 2018) - Swendeman, Steven L.; Hla, Timothy
Abstract : Sasaki and colleagues[1] ( JCI Insight 2018;3, e96902) identified the leukocyte inflammatory lipid mediator leukotriene B4 (LTB4)/LTB4 receptor 1 receptor-signaling axis in M2 macrophages as a causal pathway for the vascular endothelial growth factor-dependent pathological neovascularization in a mouse model that mimics wet age-related macular degeneration. This observation provides a novel mechanism by which an eicosanoid lipid mediator drives retinal vascular pathology and suggests a novel therapeutic target for proliferative retinal vascular diseases.